دراسة حالة عن ميول طلبة في تعلم اللغة العربية بالمدارس المتوسطة الإسلامية بمالانج وباتو - Murdiono Murdiono (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2018)
The research aims to discuss the motivation of students (Case Study) in Madrasah Tsanawiyah Negeri (MTs.N) 1 Malang, Madrasah Tsanawiyah Negeri (MTs.N) Batu, Madrasah Tsanawiyah (MTs.) Surya Buana Malang unfortunate to learning Arabic. The methodology used by the researchers in this study is a quantitative method. As for the results of the students' responses to three aspects, namely cognitive, effective and concentration aspects through filling in student motivation questionnaires, interviews, and observations in learning Arabic as a whole of MTs.N Batu 2.76%, that can be grouped into medium. Then aspects of the student's interest in learning Arabic are overall average in MTs.N 1 Malang 2.71% so that the poor can be grouped in category medium, and aspects of the student's interest in learning Arabic as a whole on average in MTs. Surya Buana are 2.67% so it can be grouped in group Medium. Based on the analysis of data that has been discussed that the interest of students in MTs.N 1 Malang, MTs.N Batu, MTs. Surya Buana are classified into group Medium.